Knowledge on hypertension and its management among family member in Pokhara Metropolitan City. - Pandey,Sony (2020)
ABSTRACT: Introduction: Hypertension as a silent killer is a noteworthy public health concern worldwide due to its significant contribution to the global health burden and its role as a prominent risk factor for the development of a number of disease processes. It is well known that lifestyle factors play a crucial role in the development of HTN and future steps need to be taken to provide interventions that improve lifestyle factors. Empirical evidence has suggested that social support from family and friends can help patients take their medicines correctly. Methods: A cross-sectional study was conducted in Pokhara Metropolitan City among 236 family members of hypertensive patients. An adapted tool with certain modification was applied for data collection. Multiple logistic regression analysis was used to find out the association between knowledge on hypertension, its management and socio demographic variables. Results: Among the study respondents more than three fourth (76.3%) of them were female. Almost all (96.6%) of the respondents had heard about hypertension and one third (33.4%) of the respondents had heard about hypertension from television. More than half (62.7%) of the respondents did not have family member having hypertension. The present study showed that almost three fourth of the respondents 185(78.4%) had knowledge on hypertension and nearly all of the respondents 227(96.2%) had knowledge on management of hypertension. The socio-demographic variable educational status and the respondents who have heard before about hypertension were found to be associated with knowledge on hypertension. Similarly, the respondents who have heard before about hypertension were found to be associated with knowledge on management of hypertension. Respondents having formal educational status were 3.5 times more likely to have adequate knowledge (AOR:2.9, p:0.013, CI:0.855-10.122) and respondents having bachelor and above educational status (AOR:10.9, p:0.01, CI:2.609-45.500). Conclusion: The study concluded that the most of the respondents had knowledge on hypertension as well as in management of hypertension. The education status and those who have heard about hypertension before were found to be associated with knowledge on hypertension. Thus, family member interventions can be done to manage and control the emerging non-communicable diseases in the community. Keywords: Hypertension, Knowledge, Management knowledge, Family member and Pokhara Metropolitan City